Respuesta :
To answer this, set up a system of equations.
We know that Jordan's age, y, plus Alex's age, x, is equal to 33
x+y=33
We also know that Alex's age, x, is equal to Jordan's age, y, plus 7
x=y+7
Substitute (y+7) in for x. You can do this because y+7 is equal to x
y+y+7==33
Combine like terms
2y+7=33
Subtract 7 from each side
2y=26
Finally divide each side by 2
y=13
Jordan is 13 years old.
Plug 13 in for y in the second equation.
x=13+7
x=20
Alex is 20 years old
To check your answer, plug both ages in to true other equation.
20+13=33
33=33
Alex=20 years old
Jordan=13 years ild
We know that Jordan's age, y, plus Alex's age, x, is equal to 33
x+y=33
We also know that Alex's age, x, is equal to Jordan's age, y, plus 7
x=y+7
Substitute (y+7) in for x. You can do this because y+7 is equal to x
y+y+7==33
Combine like terms
2y+7=33
Subtract 7 from each side
2y=26
Finally divide each side by 2
y=13
Jordan is 13 years old.
Plug 13 in for y in the second equation.
x=13+7
x=20
Alex is 20 years old
To check your answer, plug both ages in to true other equation.
20+13=33
33=33
Alex=20 years old
Jordan=13 years ild